First records of the Chihuahuan Black-headed Snake, Tantilla wilcoxi Stejneger, 1902 (Squamata: Colubridae), in the Mexican state of Jalisco - Rubén Carbajal-Márquez; José Arenas-Monroy; Gustavo Quintero-Díaz; Zaira González-Saucedo; Christian García-Balderas (Check List, 2015)
Based on three specimens, we document the occurrence of Tantilla wilcoxi in the Mexican state of Jalisco. This species was found at two localities, 2.9 km apart, both in the ecotone between xerophytic scrub and oak forest in the arid plains of the municipality of Ojuelos de Jalisco in the northeastern portion of the state.